Mengukur Efisiensi Operasional Bank Publik Di Indonesia - Calista, Avissa; Pribadi, Firman (208-7721)
The impact of the global crisis in the banking sector, prompting banks in Indonesia, for efficiency. Bank in saying achieve efficiencies in scale when the relevant bank is able to operate in a constant returns to scale (constant returns to scale), while the efficiency of coverage is achieved when a bank is able to operate in diversified locations. Location efficiency is achieved when a bank is able to determine a wide range of output that maximizes profit, on the one hand banks seek to improve its performance by improving the acquisition of public funds but on the other hand as the intermediary distribution in the form of loans is not maximized. Efficiency relates to the cost of that is issued by a bank, where the conduct efficient operations can be in the know and in measuring the ability of management to manage input and output. Based on this background, this study aims to determine the effect of total deposits, loans (loans), total assets, total cost, NPA, total revenue and spread to the operating profit. To determine the influence of ROA, NIM, NPL, ROA, LDR and CAR to profitability. To test the operational efficiency of banks in Indonesia with DEA method (Data Envelopment Analysis). Object of research is that Go Public Bank in Indonesia in the period 2010 - 2014. The sampling technique used purposive sampling technique. Data types are Sekuder data, source data from the website BEI (www.idx.co.id). Data collection techniques and methods of documentation methods literature. Regression analysis data analysis, hypothesis testing and DEA method.The results showed that simultaneous total deposits, loan / credit is given, total assets, total cost, NPA, total revenue and spread significant and positive impact on operating profit. In partial successfully received or no significant effect on operating profit are deposits, loan / credit is given, total assets and total revenue, whereas no significant effect is the NPA. The most dominant variable affecting the operating profit is total deposits. Simultaneously ROA, NIM, NPL, ROA, and LDR CAR significant and positive impact on profitability. In partial successfully received or no significant effect on profitability is ROA, NPL, LDR and CAR, whereas no significant effect on profitability is NIM and ROA. The most dominant variable affecting profitability is the LDR. DEA was able to identify nine major banks from 14 banks, and small banks 5 of 14 banks are efficient.